Pharmacological characterization of Cirsium ligulare Boiss. (Asteraceae) herb decoction - Dobrić, Silva; Petrović, Silvana; Kukić-Marković, Jelena; Samardžić, Stevan; Milutinović, Violeta (Vojnosanitetski pregled, 2017)
Background/Aim. Data on phytochemical and pharmacological investigations of genus Cirsium Mill. (Asteraceae) are scarce. Some data suggest that decoctions or infusions prepared from these plants are used in folk medicine as tonics, particularly in inflammatory, liver and stomach diseases. So far there have been no pharmacological investigations related to Cirsium ligulare (C. ligulare) Boiss. Accordingly, the aim of this study was to estimate antioxidative, anti-inflammatory and gastroprotective activities of aqueous extracts of C. ligulare herb prepared as 5% and 10% decoctions. Methods. Antioxidative activity was determined using the method of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging. Investigations of anti-inflammatory (a model of systemic inflammatory response induced by endotoxin of Escherichia coli and carrageenan-induced rat paw oedema model for local inflammatory response), as well as gastroprotective effects (a model of stress-ulcer induced by absolute ethanol), were conducted in adult female Wistar rats that were given the aqueous extracts of C. ligulare herb per os. Indomethacin and ranitidine were used as reference drugs for evaluation of local anti-inflammatory and gastroprotective effects, respectively. Results. The results demonstrated that aqueous extracts of C. ligulare herb produced strong antioxidative activity, diminished body weight loss induced by endotoxin, significantly reduced carrageenan-induced paw oedema, and prevented the ulcerogenic action of absolute ethanol. Both anti-inflammatory and gastroprotective activities of the extract tested were comparable to those of the reference drugs. Conclusion. Presented results justify the traditional use of C. ligulare herb decoctions and further phytochemical and pharmacological investigations are warranted.
Keywords: cirsium; asteraceae; pharmacologic actions; herbal medicine; rats; wistar